Lebanon: - Arfan Johan Wihananto; Yon Machmudi (Indonesia Center for Middle East Studies, 2021)
This article aims to analyze the efforts of the Lebanese government to position the Lebanese Armed Forces (LAF) as the primary defence force in ensuring the country's sovereignty. The LAF, as a regular military institution, competes with the power of Hezbollah, so that this phenomenon becomes a challenge for the Lebanese government domestically and internationally in fighting for public legitimacy, apart from issues of collusion and dependence on the existence of internal actors and external interventions. This article also provides recommendations for solutions based on observations during the author's assignment to Operation World Peace in Lebanon (UNIFIL) in 2010 and 2018. This article is expected to contribute to the development of empirical and academic literature on the political situation in Lebanon. It also offers lessons from a country with a heterogeneous demographic background faced with conflict and power dynamics.